1986
DOI: 10.1111/j.1748-1716.1986.tb07991.x
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode recordings from the facial nerve in man

Abstract: Microneurographic recordings have for the first time been obtained from the human facial nerve trunk, close to its exit from the stylomastoid foramen. The aim was to search for evidence of an afferent or sympathetic component of the facial nerve at this level and to study the fascicular organization of motor fibres. Single unit discharges of motor axons were occasionally discerned, and all recordings showed multiunit motor impulses preceding the EMG activity of the appropriate facial muscles by about 5 ms duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…Since sympathetic fibres run along the internal carotid artery before passing to the ophthalmic nerve (Parkinson, Johnston & Chaudhuri, 1978), it is conceivable that some of them accompany the ophthalmic artery to reach the forehead with its terminal branch. The high rate of success with which sympathetic activity was recorded in the present study underlines the significance of our previous failures, with the same technique, to detect sympathetic activity in the human infraorbital and facial nerves (Nordin, Hagbarth, Thomander & Wallin, 1986;Nordin & Thomander, 1989). By exclusion, these negative findings suggest that all sympathetic fibres reach the infraorbital nerve territory by joining branches of the external carotid artery (cf.…”
Section: Absence Of Vasoconstrictor Activity In the Supraorbital Nervesupporting
confidence: 66%
“…Since sympathetic fibres run along the internal carotid artery before passing to the ophthalmic nerve (Parkinson, Johnston & Chaudhuri, 1978), it is conceivable that some of them accompany the ophthalmic artery to reach the forehead with its terminal branch. The high rate of success with which sympathetic activity was recorded in the present study underlines the significance of our previous failures, with the same technique, to detect sympathetic activity in the human infraorbital and facial nerves (Nordin, Hagbarth, Thomander & Wallin, 1986;Nordin & Thomander, 1989). By exclusion, these negative findings suggest that all sympathetic fibres reach the infraorbital nerve territory by joining branches of the external carotid artery (cf.…”
Section: Absence Of Vasoconstrictor Activity In the Supraorbital Nervesupporting
confidence: 66%
“…Recordings have been made from afferent myelinated fibres in the infraorbital nerve (Nordin, Hagbarth, Thomander & Wallin, 1983;Johansson, Trulson, Olsson & Abbs, 1988 a; Johansson, Trulson, Olsson & Westberg, 1988b;Nordin & Hagbarth, 1989;Nordin & Thomander, 1989), from sympathetic C fibres in the supraorbital nerve (Nordin, 1990) and from motor fibres in the facial nerve trunk (Nordin,Hagbarth,MS 8186 Thomander & Wallin, 1986). The present study on afferent C fibres in the supraorbital nerve provides the first proof of the presence of low-threshold C mechanoreceptors in humans and also establishes the existence of mechano-heat nociceptors in the forehead.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although phylogenetically the role of the perioral region in environmental exploration has become less important with the evolution of the upper limb, this region remains pivotal for activities such as speech, chewing and swallowing. Accordingly, microneurographic studies in humans (Nordin et al ; Trulsson & Johansson, ) have shown that mechanoreceptive afferents supplying the orofacial area (hair follicle fibers, fast‐adapting receptors, and type I and type II slow‐adapting receptors and afferent fibers) are strongly activated by mechanical stimulation due to contact between the lips, changes in air pressure during the speech and skin and mucosa deformations during chewing and swallowing activities.…”
Section: Discussionmentioning
confidence: 99%